Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Perusahaan Perbankan Bursa Efek Indonesia - Anastasya Giacesita; Vhika Meiriasari; Reny Aziatul Pebriani (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to investigate the effect of cash turnover and transaction turnover on profitability in banking companies listed on the Indonesia Stock Exchange (BEI) 2015- 2019. The data used is secondary data from the company's financial statements. Purposive sampling technique was used in the sampling process and collected 15 private banking companies, which were then analyzed using multiple linear regression. The results showed that cash turnover had a negative effect on profitability. However, receivables turnover proved to not affect profitability. This research is expected to provide insight for banking companies to pay attention to cash turnover if they want to increase profitability